University students’ perceptions on inter-ethnic unity among Malaysians: situational recognition, social self-construal and situational complexity - Arina Anis Azlan,; Chang, Peng Kee; Mohd Yusof Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
National unity is pertinent to the stability and progress of a country. For multi-ethnic nations such as Malaysia, diversity is perceived as a challenge to national unity. Extant literature shows that the different ethnic groups in Malaysia have expressed different ideals on inter-ethnic unity and differ in their ideas on how it may be achieved. To what extent do these differences exist? The purpose of this research was to investigate the perceptions of inter-ethnic unity in Malaysia among the three main ethnic groups. A survey measuring perceptions on the issue of inter-ethnic unity was distributed among 575 university students at four different institutions of higher learning in the Klang Valley, Malaysia. The results show that the different ethnic groups held similar problem perceptions in terms of problem recognition, involvement, constraint recognition, and did not differ significantly in terms of their social position on the problem. There were however, significant differences between the Chinese and Malay/Bumiputeras, as well as between the Chinese and Indians when it came to perceived level of knowledge and experience about the problem. The findings indicate that different ethnic groups may be differently equipped to handle the issue of inter-ethnic unity in Malaysia. Communication and policy efforts to build an integrated nation would benefit from taking these differences into consideration to ensure effective implementation.